Agility in marketing: a bibliometric analysis - Thümler, Nico (Business: Theory and Practice, 2023)
Research on agility in marketing has been shaped by a great number of articles published in recent decades. My research contributes to the literature by examining the basis of different intellectual frameworks and by identifying relevant references, authors, topics, and journals for the matter. With this focus, I used bibliometric techniques to investigate over 1,200 articles published between 1992 and 2022. I regarded publication periods that shaped the progression of the research subject. Results show that there are 75 relevant publications. Those could be divided into three research streams. The first stream considers frameworks and agile supply chains, the second IT infrastructure to improve enterprise agility, and the third enterprise and organizational agility in general. I applied a historical perspective, identified the social, intellectual, and conceptual structure of marketing agility research.